ANALISIS KESULITAN BELAJAR MATEMATIKA MATERI PENGOLAHAN DATA PADA SISWA KELAS V SD - Ali Muckromin; Rini Budiwati; Ani Budiarti; Budi Murtiyasa; Sumardi Sumardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Research procedures with a qualitative approach (naturalistic). The information collection methods used were questionnaires, interviews, observation and documentation during mathematics education activities on data processing materials. With research subjects participating in class V SDN 2 Banyusri as many as 15 children consisting of 6 men and 9 women. Information analysis using the triangulation method and the accuracy of the observer. The purpose of this research is to analyze aspects of learning difficulties in mathematics data processing materials in fifth grade elementary school students. Research results include aspects of internal learning difficulties 46.67% and aspects of external learning difficulties 50.00%. Internal and external aspects 48, 34%.